(3QSGdI aj JQLeI GHf SjfG hagQSI cJHgs - (3GdLhRLGfj , YHO GdhGMO GdLhRLGfj, CHh YHjO,J (B428 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI bGd CHh YHjO MOKfj CHh Ydi bGd cGf hGdOj QLdkG ef Cgd HdN hGfJbd efgG Edi ai CjGe GdCejQ aQM Hf efUhQ s
(3BNQgG (B:s
(3aYGhOJg GdYdI ai GdWQjb Edi Cf hUd dgePGf hYde Cf bhJg bO SbWJ hCfgeG dG Jaj HOaY GdeQV aCged eOGhI s
(3Vef eLehY , JQJjHgG (B: 11s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B207s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ , JGeI s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs